Can an effective SARS-CoV-2 vaccine be developed for the older population? - Graham Pawelec (Immunity & Ageing, 2020)
Abstract The emergence of SARS-CoV-2 and its inordinately rapid spread is posing severe challenges to the wellbeing of millions of people worldwide, health care systems and the global economy. While many younger people experience no or mild symptoms on infection, older adults are highly susceptible to life-threatening respiratory and systemic conditions which demand a full understanding and leveraging of knowledge of the differences between immunity in young and old people. Consequently, we welcome papers addressing any issues relevant to immunity and ageing in the context of SARS-CoV-2, and will endeavour to fast-track peer-review. We aim to provide a platform exclusively for discussions of individual and age differences in susceptibility and immune responses to COVID caused by SARS-CoV-2 infection and how to prevent or reduce severity of disease in older adults.